New Digital Audiences. From Mediations to Swarms - Cuadra, Álvaro (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
This article is a theoretical reflection from the Latin American tradition in communication studies that aims to explore the epistemological limits and the political scope that the emergence of new digital audiences implies. From our perspective, the socio-cultural look in the wake of the Frankfurt School deserves be reviewed in the light of profound technological advances. Currently, digital audiences appear as hybrid subjects, born from the conjunction of a Consumer Society and an Information Society. These new subjects, "user-consumers" inhabit the RSO, online Social Networks, constituting unstable, ephemeral, emotional, depoliticized "swarms".
Keywords: Consumers; Users; Digital Swarms; Info